Renewable Energy Source Enactment for Speed Control of BLDC Motor with Proportional Integral (PI) Controller - Soedibyo Soedibyo; Muhammad Budi Rahayu Widodo; M. Ashari (JAREE (Journal on Advanced Research in Electrical Engineering), 2020)
This paper present about speed control of Brushless Direct Current (BLDC) Motor 1 kW in which supplied using Photovoltaic (PV) Array 1.5 kW that simulated using MATLAB 2016a.  Speed control of BLDC exactly depend on voltage condition, so speed control mean voltage control. Furthermore, Proportional Integral (PI) controller will be implemented to get best performance of the system during irradiance change or some load implemented. For detail analysis purpose, the simulation will do in some case such by vary irradiation of PV, Vary the speed reference then vary of load. From simulation result we get the information that dynamic irradiance, load and speed reference will influence the response stability of speed so do Power Consumption, Voltage and Current response.Keywords: brushless direct current (BLDC) motor, photovoltaic (PV), proportional integral (PI) controller.